Demographic Factors and Employee Performance: The Mediating Effect of Employee Empowerment - Arief Tukiman Hendrawijaya (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2019)
This study analyzes the influence of age, gender, education, years of service, and number of family dependents on employee empowerment both directly and indirectly through employee performance. The sample was taken from 14 cigar companies in Jember Regency, East java, Indonesia, of which each company is represented by ten samples (respondents) who are randomly selected. The samples consist of 140 people. The study uses path analysis to determine the direct and indirect effects of the variables. The results showed that age, sex, education, years of service, and number of family dependents have a significant positive effect on employee performance and on employee empowerment. Employee performance mediates the effect of age, sex, education, years of service, and number of family dependents on employee empowerment.